Effect of Different Calcium Precursors on Biomimetic Hydroxyapatite Powder Properties - Karakas, A.; Yoruc, A. B. Hazar; Erdogan, D. Ceylan; Dogan, M. (POLISH ACAD SCIENCES INST PHYSICS, 2012)
Hydroxyapatite is the main component of human hard tissues such as bones and teeth. Because it has a great biocompatibility with human organism, it is used as biomaterial with the purpose of form and repair hard tissues. Hydroxyapatite is formulated as Ca-10(PO4)(6)(OH)(2) and shows high stability under physiological conditions. In this study, biomimetic hydroxyapatite powder has been synthesized using by synthetic body fluids which has the same composition as human blood plasma. Moreover, the effect of different precursors on properties of synthesized powders has been investigated. For that purpose calcium nitrate tetrahydrate [Ca(NO3)(2)center dot 4H(2)O], calcium chloride [CaCl2], calcium hydroxide [Ca(OH)(2)] and diammonium hydrogen phosphate [(NH4)(2)HPO4] were used as precursors. Mainly literature focused on the synthesis of hydroxyapatite powders was carried out using chemical method. However, in this study, the synthesis of hydroxyapatite powder is carried out using biomimetic method. Chemical structures of synthesized powders have been investigated by the Fourier transform infrared and X-ray diffraction methods. Results showed that synthesized powders have a pure hydroxyapatite structure. Surface area of the synthesized powders was measured by the Brunauer-Emmett-Teller method. Morphological structures have been characterized by using scanning electron microscopy. Furthermore, particle size of powders was calculated using the Brunauer-Emmett-Teller method. It was clearly seen that morphological properties of biomimetic hydroxyapatite have affected the use of different calcium precursors.
Keywords: MECHANICAL-PROPERTIES; Physics